Synthesis and characterization of platinum free, conducting polymer based counter electrode for dye sensitized solar cell (DSSC) / Usman Ahmed - Usman , Ahmed (2019)
Among all photovoltaic devices, dye sensitized solar cell (DSSCs) are assumed as one of the most potential renewable energy source (device), due to facile fabrication methods, cost-effectiveness and environmentally friendly behavior. Certain constituents such as photoanode (conventionally titanium dioxide), counter electrode (mostly platinum), sensitizing dye (different kinds including natural and organic dyes) and electrolyte (iodide and tri-iodide) effects the photovoltaic performance of DSSCs. Each component has its own importance but among all, counter electrode also plays a vital role. Counter electrode receives the electron from an external load and transfer them towards the electrolyte for redox reaction. The dye accepts these electrons which helps in the regeneration of dye electron. All these components significantly affect the overall performance of DSSC. Various materials including carbon-based materials, oxides, sulfides, and conducting polymers have been explored as cost effective, stable and highly efficient material for the possible replacement of Pt-based counter electrode (CE) in DSSCs. Recently, researchers are investigating different nanocomposite-based hybrid material as counter electrode for DSSC. It was found that the composite materials possessing high catalytic property of reduction, high surface area toward the flow of electron and low charge transfer resistance showed great potential for the replacement of Pt based CE. In this work, conducting polymer have been studied as counter electrode for DSSC. To examine the structural, chemical composition, optical behavior and photovoltaic performance, Field Emission Scanning Electron Microscopy (FESEM), X-ray powder diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), Ultraviolet–visible spectroscopy (UV-vis) and electrochemical analysis has been studied. The photovoltaic performance test has been studied to examine the current density vs voltage (J-V), and the power conversion efficiency (PCE) of DSSC under standard test conditions. It was observed that with the addition of strontium titanite (SrTiO3) in polypyrrole (PPy) nanocomposite the photovoltaic performance of DSSC has been enhanced. PPy achieved the power conversion efficiency value of 1.29% but with the increment of SrTiO3, hybrid polypyrrole nanocomposite PPy-SrTiO3-25%, PPySrTiO3-50% and PPy-SrTiO3-75% attained the PCE of 1.98 %, 2.52% and 2.08% respectively. Furthermore, in comparison with Pt based CE (2.17%), PPySrTiO3-50% showed enhanced PCE that is 2.17% and 2.52% respectively. In another project, polyaniline (PANI) was used as conducting polymer to fabricate the counter electrode for DSSC. Different concentrations of PANI were taken in order to optimize the concentration of PANI nanoparticles for further studies. PANI due to its unique properties also showed great potential as CE for DSSC. It was noticed that unaided PANI with the concentration of 20mg/ml showed enhance photoelectrochemical response as compare to PANI-1 and PANI-2. The electrocatalytic and photovoltaic performance of PANI-3 can be enhanced with the addition of metal oxide, transition metals and carbonaceous materials and with other materials.